Manajemen Cyber Public Relations Instagram Dalam Membangun School Branding - Maryam, Rima; Hendrowati, Tri Yuni; Aswad, Fatqul Hajar; Mu'in, Juhri Abdul (Universitas Islam Negeri Raden Intan Lampung, 2026)
The development of school branding at the elementary school level in the digital era is strongly influenced by a school’s ability to manage public communication strategically and sustainably. Cyber Public Relations (CPR) through social media has become an essential medium for schools to disseminate information, build a positive image, and enhance public trust. This study aims to analyze the implementation of CPR through Instagram in building School branding at UPT SD Negeri 3 Pringsewu Barat, focusing on planning, organizing, implementation, supervision, and the challenges encountered. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving the principal, public relations coordinator, teachers, social media administrators, and students’ parents. Data validity was ensured through source, technique, and time triangulation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of CPR through Instagram has been carried out and has contributed to the development of School branding; however, it has not yet been implemented optimally and sustainably. The main obstacles include limited human resources, time, and budget, as well as the absence of formal written planning and an established public relation's organizational structure. It can be concluded that strengthening School branding requires well-planned, collaborative, and sustainable CPR management supported by clear policies and the enhancement of digital competencies among school stakeholders.